2021
DOI: 10.1080/2090598x.2021.1957410
|View full text |Cite
|
Sign up to set email alerts
|

Penile reconstruction: An up-to-date review of the literature

Abstract: Objective: : To review the literature on adult penile reconstruction due to Peyronie's disease, trauma and cosmesis, while emphasising specific surgical techniques and procedures such as phalloplasty, radial forearm free flap reconstruction, and penile transplant. Methods: : A comprehensive review of the literature for the years 1992-2020 of the PubMed and SpringerLink databases was performed to identify articles on penile reconstruction. Search terms included 'penile reconstruction', 'penile trauma', 'phallop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Principles of penile reconstruction surgery are: Judiciously debride necrotic tissue, anastomose the severed urethra, repair the tunica albuginea and microsurgical repair for the dorsal nerves, arteries and veins[ 2 , 15 - 17 ]. Ottaiano et al [ 18 ] summarized in a review of the literature on reconstruction that immediate reconstruction of penile injuries typically occurs by means of suspension or entrapment can reduce complications[ 18 ]. Recent publications have investigated the anatomical approaches to penile allografts and suggested that connection of cavernosal, dorsal, and pudendal arteries would allow for optimal reperfusion[ 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Principles of penile reconstruction surgery are: Judiciously debride necrotic tissue, anastomose the severed urethra, repair the tunica albuginea and microsurgical repair for the dorsal nerves, arteries and veins[ 2 , 15 - 17 ]. Ottaiano et al [ 18 ] summarized in a review of the literature on reconstruction that immediate reconstruction of penile injuries typically occurs by means of suspension or entrapment can reduce complications[ 18 ]. Recent publications have investigated the anatomical approaches to penile allografts and suggested that connection of cavernosal, dorsal, and pudendal arteries would allow for optimal reperfusion[ 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Correction rate for curvature range between 42 and 100%, with overall satisfaction varying from 68 to 100% [ 22 ]. The shortening procedures are associated with shortening of penis up to 2.5 cm [ 23 ]. Approximately 1 cm of penile shortening is expected for every 20 degrees of correction after penile plication surgery [ 24 ] (Table 1 ).…”
Section: Management Of Patients With Complex Curvature In Peyronie’s ...mentioning
confidence: 99%